Italian Opera Houses and Festivals - Lynn, Karyl Charna (Rowman & Littlefield Publishers, 2005)
Italian Opera in the 18th and 19th centuries was an experience unequaled anywhere else in the world. The unique emotion, flavor, and passion that existed have yet to be attained in any other country. Opera houses in Italy are the birthplace of this great art form. They represent its beauty and richness. More than just concrete, stone, glass, and wood, they are alive, each with a character and history of its own. This work recreates the social, political, architectural, and performance histories of each house by including eyewitness accounts from Italian newspapers, journals, and books of the time. It covers more than 50 Italian opera houses and festivals, organized by their city of origin and geographic region. Each chapter is a journey back in time, beginning with the first theaters and performances in the city and concluding with an architectural description of the principal theater and a practical information guide for visitors (including hotel recommendations). The operatic activities of the main theater, including inaugurations, important performances, and world premieres, are also covered. A photospread, along with brief descriptions of opera-related sites, including the birthplaces, dwellings, and museums of Italy's greatest composers, give an even more complete portrait of the art.